Integrasi Java Message Service (Jms) Dengan Message-Driven Bean Pada Teknologi Java Ee - Wiharto Wiharto (Jurnal Ilmiah SINUS, 2009)
There are three a part of Enterprise Java Bean (EJB) architecture in the Java Enterprise Edition (Java EE) technology. First, session bean, entity bean and the last message driven bean (MDB). Session bean is a bean that can be accesed by remote method invocation (RMI) for give ability, it provided business interface. Entity bean representing and manipulating data which persistent in that application. For acces that entity bean, it also provided business interface as the same with session bean. Message driven bean is one of component in the EJB which has an unique characteristic, it is whitout bisnis interface, so client can not be accesed with the RMI, it can be only accesed with the messaging system like java message service (JMS).Kay words : EJB, RMI, Java Message Service.